Manage me a proposed project management application for senior visual communication students who freelance in digital design and illustration - Azarcon, Kyle V.
Senior visual communication students who freelance in digital design illustration in University of the Philippines Diliman often feel overwhelmed and pressured by the multiple tasks, and meeting deadlines for both school and freelancing work requires excellent organizational skills, and addressing these challenges requires careful planning.